EDUKASI DAN SKRINING ANEMIA MELALUI PEMERIKSAAN KADAR HEMOGLOBIN PADA REMAJA SMA MUHAMMADIYAH 23 JAKARTA - Ratih Kartika Dewi; Engla Merizka; Herlina; Tantri (Politeknik 'Aisyiyah Pontianak, 2023)
Anemia occurs when there aren't enough healthy red blood cells in your body's organs. This condition occurs due to a lack of hemoglobin (an iron-rich protein) which affects the production of red blood cells. Anemia is a health problem throughout the world and currently the prevalence of anemia in adolescents is still high. The impact of anemia on teenagers is a decrease in: productivity, fitness, concentration, and decreased immunity as well as disrupting growth. Lack of knowledge from both children and parents, even community and Health programs created by the government unequally distributed are also the reasons why this problem cannot be resolved. This activity aims to increase knowledge of students at SMA Muhammadiyah 23 Jakarta regarding anemia and to screening anemia by checking hemoglobin levels as an early detection of anemia. The method used is interactive lectures and group discussion. Hemoglobin measured by Point of Care Testing (POCT) method. Data analysis showed that there was a significant difference between before and after providing anemia screening education to students at SMA Muhammadiyah 23 Jakarta (p<0.05) with the average before being given the education being 43 to 83 after the education. The results showed 12.2% male student have low Hb levels, while 43.4% of female students have low Hb levels. So health education regarding anemia screening was successful in increasing the knowledge of students at SMA Muhammadiyah 23 Jakarta and 185 respondents showed that 55.6% of participants have low Hb levels.